Protein enrichment of guava residue (Psidium guajava L.) through semi-solid fermentation (Research, Society and Development, 2021)
The residues resulting from agro-industrial activities come mainly from the processing of fruit for the production of pulp. The use of these residues is shown in the face of food waste as a great opportunity for the development of by-products. Among the different agro-industrial residues, the guava residue stands out for presenting in its composition vitamins, minerals, fibers and antioxidant compounds that are important for physiological functions. The objective of this work was to study the process of protein enrichment of guava residue using the yeast Saccharomyces cerevisiae, through semi-solid fermentation. The guava residue was crushed and then placed in a rectangular bioreactor with 12% m/m of yeast and stored in an oven with forced air circulation at 35 °C temperature for 21 hours. These samples were weighed at intervals of 0, 3, 6, 9, 12, 15, 18 and 21 hours of fermentation and the analyzes of water, protein and total soluble solids content were monitored at each interval. In general, it is possible to conclude that the semi-solid fermentation used in the guava residue, with the use of the yeast Saccharomyces cerevisiae, allowed the increase in the residue's protein content with the fermentation time, with the highest concentrations at 3 and 6 hours. Thus, it is possible to affirm that the technique used was satisfactory in the protein enrichment of the guava residue, and it can be used as a form of waste recovery.